Efficacy of early thoracoscopic debridement for syn-pneumonic pleural effusions in pediatric age group - Grandhi, Kiran; Kokiwar, Prashant (International Journal of Advances in Medicine, 2019)
Background: Pleural effusion can be treated by antibiotics alone but thoracoscopy assisted debridement has proved superior to antibiotics alone. There is need to study this aspect in more details related to the superiority of the treatment. The objective was to study efficacy of early thoracoscopic debridement for syn-pneumonic pleural effusions in pediatric age group. Methods: A hospital based follow up study was carried out among 40 children of 1-7years of age. They were divided into two groups. One group with 15 children received only antibiotics while the other group with 25 children received thoracoscopic debridement. The results were compared in terms of hospital stay and clinical outcome. Results: It was found that the hospital stay was significantly shorter in children who received thoracoscopic debridement compared to antibiotic group. The chest X-ray was normal in all cases who received thoracoscopic debridement compared to antibiotic group. Decortications were required in five children in antibiotic group compared to none who received thoracoscopic debridement. There was no morbidity and mortality in the children received thoracoscopic debridement. Clinical and symptomatic relief was much better in children received thoracoscopic debridement compared to antibiotic group where there was persistence of the symptoms. Conclusions: Thoracoscopy done in 3days of syn-pneumonic effusions give better out come in terms of hospital stay, morbidity, radiological resolution, compared to thoracocentesis done cases.